(untitled) (Journal of Student Affairs in Africa, 2021)
The recurrence of xenophobic violence in South Africa has been attributed to the proliferation of antimigrant sentiments that stems from social, political, economic and cultural misconceptions and cleavages. The study presents the results of a survey undertaken at the Durban University of Technology (DUT) to investigate the perceptions and attitudes of DUT students on xenophobia in South Africa. A questionnaire was designed and employed to collect data from 547 registered students of a university in Durban. The result reflects the existence of satisfactory awareness on xenophobia and low levels of anti-migrant sentiments which show that the majority of the students are not xenophobic. Traces of xenophobic perceptions and attitudes were observed in the responses of entry-level students from low-income areas, thus pointing to entry-level students and younger students as being more disposed to xenophobic tendencies. This trend echoes normative conceptions concerning xenophobia in South Africa, particularly, as a phenomenon deeply ingrained in socioeconomic inadequacies. However, the positive disposition of most students towards xenophobia reaffirms the importance of educational institutions in intercepting negative ethnic/racial sentiments as well as calls for intensified integration programmes and the extension of such into the communities.